Crowding out informal care: evidence from a social experiment in Germany - Arntz, Melanie; Thomsen, Stephan L. (Discussion paper, 2008)
This paper evaluates the effects of a professionally assisted consumer-directed program (Personal Budgets) compared to the standard home care programs of the German long-term care insurance. The evaluation makes use of a long-run social experiment at seven different sites with a random assignment into a treatment group receiving personal budgets and a control group in standard home care programs, i.e. an in-kind benefit (agency care) and cash payments. Compared to agency care personal budgets yield better care outcomes with regard to the overall support of formal and informal caregivers. In contrast, personal budgets do not improve care outcomes compared to the much less generous cash payments due to a strong crowding out of informal by formal care.